The social programs of struggle against the extreme poverty in the province of Leoncio Prado – 2005 - Villaizán y Huerto, Jorge (2009)
The present study takes Leoncio Prado´s Province as a geographical area in the Region Huánuco. The analysis is recounted to the social programs that mothers have as mission help to raise the food and nutricional level of groups in situation of extreme poverty, focalizando as the first priority to children fron zero to 7 years, gestantes and nursing children; and as the second priority to children fron 7 to 12 years in condition (state) of malnutrition and elders in situation of social risk. These programs are: 1) The Program of the Glass of Milk, with a whole of 9,508 beneficiaries grouped in 138 Committees, and the Program of Popular Dining rooms, in number of 43 with 1,720 beneficiaries, and with an annual average of 512.400 beneficiaries, and with a whole of 17,364 shares (portions) provided in 2005. The investigation (researh) is of type descriptive Methodologically the investigation (research) is of type descriptive and for the discussion of the results the method was in use. There were in use primary sources (fountains) of information (surveys and interviews in depth) as well as records of the entities at the expense of these programs. For the processing and statistical analysis the of the SPSS was in use v. 13. The opposing results indicate the following thing: 1) The number of leaked (filtered) in the of Popular Dining rooms is 20% whereas in the Program of Glass of Milk it (he, she) is 30%; 2) During the year 2005, the level of sub coverage for the Program of the Glass of Milk was 30%, whereas for the Popular Dining rooms it (he, she) was 45 %; 3) For your (his, her, their) part, the Food program for work shows 55 % of sub coverage; 4) In all the cases, the levels of filtration are more raised in the zones by minor levels of malnutrition.